The costs of paying: Private and social costs of cash and card systems - Mats Bergman; Gabriela Guibourg; Björn Segendorf (Sveriges Riksbank, 2007)
Despite the central role of payments in theoretical and policy oriented economics, there is surprisingly little known about the costs of different payment instruments. We estimate social and private costs of cash, debit and credit card payments in Sweden in 2002. The combined social cost of providing these payment services is approximately 0.4 per cent of GDP. Debit and credit cards are socially less costly than cash for payments above EURO 8 and EURO 18, respectively. Corresponding thresholds for consumers' private costs are somewhat higher. Data indicate a too extensive use of cash relative to card payments in terms of both private and social costs.
Keywords: D12; D23; D24; 330; Cash payments; Card payments; Social costs; Private costs; Zahlungsverkehr; Kreditkarte; Elektronisches Geld; Soziale Kosten; Schweden